The role of comorbidities (hypertension, obesity and diabetes) in the expression of the ACE 2 receptor in COVID-19: A systematic review (Research, Society and Development, 2025)
During the COVID-19 Pandemic, relationships between comorbidities and the severity of COVID-19 were highlighted, mainly related to the ACE 2 receptor, present in several organs and responsible for regulating the renin-angiotensin system. The entry of SARS-CoV-2 into cells deregulates ACE 2, which increases inflammation and clotting, worsening the infection. Comorbidities such as hypertension, obesity and diabetes increase the risk of complications, making it essential to understand how these conditions influence the progression of the disease. The objective was to carry out research on the role of comorbidities (hypertension, obesity and diabetes) in the expression of the ACE 2 receptor in COVID-19. A systematic review of the literature was carried out that followed the PRISMA guidelines and analyzed studies published between 2017 and 2022 in the Web of Science, Scielo and PubMed databases. After rigorous screening, 15 articles were selected for the final review. The results showed that obesity is associated with a worse prognosis in COVID-19, with reduced expression of ACE 2 in adipose tissue after weight loss, reducing susceptibility to the virus. In the case of diabetes, patients with inadequate glycemic control and cardiovascular complications were at higher risk of complications. In relation to hypertension, the dysregulation of angiotensin II by SARS-CoV-2 contributes to lung damage, worsening the disease. In relation to hypertension, the dysregulation of angiotensin II by SARS-CoV-2 contributes to lung damage, worsening the disease. The study concludes that increased expression of ACE2 in patients with these comorbidities worsens the infection. Weight loss can improve ACE 2 receptor regulation. However, more studies are needed, especially in the elderly, to assess the impact of these conditions on COVID-19 mortality.